Growth signals employ CGGBP1 to suppress transcription of Alu-SINEs. Issue 12 (17th June 2016) - Agarwal, Prasoon; Enroth, Stefan; Teichmann, Martin; Jernberg Wiklund, Helena; Smit, Arian; Westermark, Bengt; Singh, Umashankar
ABSTRACT: CGGBP1 (CGG triplet repeat-binding protein 1) regulates cell proliferation, stress response, cytokinesis, telomeric integrity and transcription. It could affect these processes by modulating target gene expression under different conditions. Identification of CGGBP1-target genes and their regulation could reveal how a transcription regulator affects such diverse cellular processes. Here we describe the mechanisms of differential gene expression regulation by CGGBP1 in quiescent or growing cells. By studying global gene expression patterns and genome-wide DNA-binding patterns of CGGBP1, we show that a possible mechanism through which it affects the expression of RNA Pol II-transcribed genes in trans depends on Alu RNA. We also show that it regulates Alu transcription in cis by binding to Alu promoter. Our results also indicate that potential phosphorylation of CGGBP1 upon growth stimulation facilitates its nuclear retention, Alu-binding and dislodging of RNA Pol III therefrom. These findings provide insights into how Alu transcription is regulated in response to growth signals.